The regulation of cell wall lignification and lignin biosynthesis during pigmentation of winter jujube. (1st November 2021) - Zhang, Qiong; Wang, Lihu; Wang, Zhongtang; Zhang, Rentang; Liu, Ping; Liu, Mengjun; Liu, Zhiguo; Zhao, Zhihui; Wang, Lili; Chen, Xin; Xu, Haifeng
Abstract: Fruit lignification is due to lignin deposition in the cell wall during cell development. However, there are few studies on the regulation of cell wall lignification and lignin biosynthesis during fruit pigmentation. In this study, we investigated the regulation of cell wall lignification and lignin biosynthesis during pigmentation of winter jujube. The cellulose content decreased, while the lignin content increased in the winter jujube pericarp during pigmentation. Safranin O-fast green staining showed that the cellulose content was higher in the cell wall of winter jujube prior to pigmentation, whereas the lignin in the cell wall increased after pigmentation. The thickness of the epidermal cells decreased with pericarp pigmentation. A combined metabolomics and transcriptomics analysis showed that guaiacyl-syringyl (G-S) lignin was the main lignin type in the pericarp of winter jujube, and F5H ( LOC107424406 ) and CCR ( LOC107420974 ) were preliminarily identified as the key genes modulating lignin biosynthesis in winter jujube. Seventeen MYB and six NAC transcription factors (TFs) with potential regulation of lignin biosynthesis were screened out based on phylogenetic analysis. Three MYB and two NAC TFs were selected as candidate genes and further studied in detail. Arabidopsis ectopic expression and winter jujube pericarp injection of the candidate genes indicated that the MYB activator ( LOC107425254 ) and the MYB repressor ( LOC107415078 ) control lignin biosynthesis by regulating CCR and F5H, while the NAC ( LOC107435239 ) TF promotes F5H expression and positively regulates lignin biosynthesis. These findings revealed the lignin biosynthetic pathway and associated genes during pigmentation of winter jujube pericarp and provide a basis for further research on lignin regulation.